Factorial structure and reliability and validity of Turkish version treatment motivation questionnaire (tmq) in alcohol dependents - Evren, Cüneyt; Saatçioğlu, Ömer; Dalbudak, Ercan; Danışmant, Birim S.; Çakmak, Duran; Ryan, Richard M. (Journal of Dependence, 2006)
Object: Treatment Motivation Questionnaire (TMQ) is a 26-item self-rating scale developed by Ryan et al. (1995) for screening motivation for treatment in alcohol use disorders. Factorial analyses showed that it contains 4 factors called: (1) internalized motivation (IM), (2) external motivation (EM), (3) interpersonal-help-seeking (IHS) and (4) confidence-in-treatment (CT). The aim of this study is to determine the reliability and validity and factorial structure of Turkish translation of TMQ.Method: The study was conducted with hospitalized patients between January and July 2004 in Bakırkoy State Hospital for Mental Health and Neurological Disorders, AMA-TEM (Alcohol and Drug Research, Treatment and Education Center) in İstanbul. One hundred ninety one inpatients diagnosed as having “Alcohol Use Disorder” were included in the study. They were given sociodemographic form, TMQ and Michigan Alcohol Screening Test (MAST). The internal consistency of the Turkish version of TMQ was evaluated by the Cronbach’s Alpha test, and for validity investigation MAST was used.Results: Turkish version of the scale was found to be compatible with original scale. In alcohol dependents the internal consistency coefficient (Cronbach’s alpha) was 0.91 for IM scale, 0.42 for EM scale, 0.83 for IHS scale, 0.72 for CT and 0.84 for TMQ. For each of the items, the corrected item-total correlation values were higher than 0.30 and significant in the degree of p
Keywords: Alcohol; substance; dependence; validity; reliability; treatment motivation